Syntax circuitry: a mobile game for practicing programming language syntax - Shellington, W. A.; Rizvi, M.; Humphries, T. O.; Morsi, R. (Nazarbayev University, 2014)
According to the U.S. Bureau of Labor Statistics [1], computer science professions are among the fastest growing occupations in the U.S., and computer science occupations will add more than half a million new jobs in the next ten years. A similar need for computer professionals is expected in Kazakhstan. Simultaneously, universities in the U.S. and worldwide are seeing poor retention rates in computer science, a major reason being that students often view the early courses in the subject as uninteresting and dull [2]. Game-based learning is one of many techniques proposed to address this issue [2,3,4,5]. We have developed a mobile game that provides an engaging way for students to practice (not learn) the basic syntax of C, C++ and Java (since these languages share the same syntax for basic constructs like declarations, selection and iteration). Learning programming language syntax is a tedious process. Practicing by programming is, of course, ideal, but we believe that a game which is fun to play in their spare time will help students get used to distinguishing correct syntactical constructs quickly.
Keywords: syntax circuitry; practicing programming; language syntax